Analisis Distilasi Air Laut Menggunakan Pelat Absober Tipe Atap Memanfaatkan dengan Tenaga Matahari - Ismayati Sutina Azis; Rifaldy Ramadhan latief; Sabdha Purna Yudha (Unit Penelitian, dan Pengabdian Masyarakat (UPPM) Politeknik ATI Makassar, 2022)
The abundant and unlimited sea water in Indonesia can be used to meet human needs, but of course this requires special handling because sea water contains 3.5% salt. To use seawater as drinking water, a separation process between water and salt is required. Distillation is one of the most frequently used separation technologies, namely the separation of two or more substances based on their volatility points. The results showed that at 19:00 to 20:00 the absorber fin plate distillation apparatus with PCM produced more condensate water than the flat absorber plate distillation apparatus. The use of absorber plates with fins integrated with PCM storage contributes to the efficiency and productivity of water from the distillation system at night.